2009
DOI: 10.1002/iub.201
|View full text |Cite
|
Sign up to set email alerts
|

The HCV ARFP/F/core+1 protein: Production and functional analysis of an unconventional viral product

Abstract: Hepatitis C virus (HCV) is an enveloped positive‐strand RNA virus of the Flaviviridae family. It has a genome of about 9,600 nucleotides encoding a large polyprotein (about 3,000 amino acids) that is processed by cellular and viral proteases into at least 10 structural and nonstructural viral proteins. A novel HCV protein has also been identified by our laboratory and others. This protein—known as ARFP (alternative reading frame protein), F (for frameshift) or core+1 (to indicate the position) protein ‐ is syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 116 publications
2
43
0
7
Order By: Relevance
“…This copies the viral positive-strand RNA into a negative-strand intermediate that serves as the template for the synthesis of progeny genomes. The alternative reading frame (ARFP) or coreϩ1 and minicore proteins, with as-yet-unknown functions, appear to be synthesized from the core region by alternative translation mechanisms (6,7).…”
mentioning
confidence: 99%
“…This copies the viral positive-strand RNA into a negative-strand intermediate that serves as the template for the synthesis of progeny genomes. The alternative reading frame (ARFP) or coreϩ1 and minicore proteins, with as-yet-unknown functions, appear to be synthesized from the core region by alternative translation mechanisms (6,7).…”
mentioning
confidence: 99%
“…Recently, it was shown that HCV downregulates hepcidin expression through reactive oxygen species induction and histone deacetylase-mediated displacement of CCAAT/enhancer binding protein (C/ EBP)a and signal transducer and activator of transcription 3 (STAT3) from the hepcidin promoter, and this effect is mediated, at least partly, through core protein (Miura et al, 2008). As there is substantial evidence that core+1/ARFP acts as a transcriptional modulator (Vassilaki & Mavromara, 2009), we sought to investigate the effect of core+1/ARFP on hepcidin gene expression.…”
mentioning
confidence: 99%
“…For example, a form of the core ?1 protein was reported to be generated by initiation of translation at internal codons 85/87. This protein is shorter than that produced by the ?1 frameshift mechanism (F) and was named as core?1/S (short) [27]. Another form of this protein was also described as the ARFP/DF (double frameshift) protein.…”
Section: Introductionmentioning
confidence: 99%